Innovations in rural and agricultural finance: Community-based financial organizations: Access to finance for the poorest - Ritchie, Anne (International Food Policy Research Institute, 2010)
Community-based financial organizations (CBFOs) are user-owned and -operated groups that provide mainly saving and lending services but may also offer other financial services such as insurance. These independent organizations are based in local communities, with local governance and management. CBFOs range in size. They can take the form of informal and unregistered groups of five to seven people, usually women, who meet weekly to save small amounts of money that they then lend to each other and possibly to other members of the community. They also include larger, slightly more formal groups of up to 40 people who have written by-laws, and they include small financial cooperatives. CBFOs flourish among people who have poor access to banks and nonbank financial institutions such as microfinance institutions (MFIs).